The clamour of nationalism : Race and nation in twenty-first-century Britain - Valluvan, Sivamohan (Book collections on Project MUSE., 2019)
How does the current nationalist moment within British political culture, most acutely evidenced in the recent Brexit result, capture such a broad cross-section of constituenciess? Valluvan propose a theorisation of contemporary nationalist ascendancy which addresses this question head-on.